Structural change in response to ligand binding. - McCammon, MG; Robinson, C (2004)
The minutiae of subtle changes that occur in response to ligand binding in multiprotein complexes are often difficult to assess without resource to high resolution X-ray analysis. Recent developments in mass spectrometry, however, are providing insight into dynamic changes within components. In this article we review recent applications of MS for selection of ligands and definition of their binding characteristics for individual protein targets through to macromolecular complexes such as ribosomes.